Temporal and spatial expression of homeotic genes is important for segment-specific neuroblast 6-4 lineage formation in Drosophila. - Kang, S.Y.; Kim, S.N.; Kim, S.H.; Jeon, S.H. (Molecules and Cells, 2006)
Different proliferation of neuroblast 6-4 (NB6-4) in the thorax and abdomen produces segmental specific expression pattern of several neuroblast marker genes. NB6-4 is divided to form four medialmost cell body glia (MM-CBG) per segment in thorax and two MM-CBG per segment in abdomen. As homeotic genes determine the identities of embryonic segments along theA/P axis, we investigated if temporal and specific expression of homeotic genes affects MM-CBG patterns in thorax and abdomen. A Ubx loss-of-function mutation was found to hardly affect MM-CBG formation, whereas abd-A and Abd-B caused the transformation of abdominal MM-CBG to their thoracic counterparts. On the other hand, gain-of-function mutants of Ubx, abd-A and Abd-B genes reduced the number of thoracic MM-CBG, indicating that thoracic MM-CBG resembled abdominal MM-CBG. However, mutations in Polycomb group (PcG) genes, which are negative transregulators of homeotic genes, did not cause the thoracic to abdominal MM-CBG pattern transformation although the number of MM-CBG in a few per-cent of embryos were partially reduced or abnormally patterned. Our results indicate that temporal and spa-tial expression of the homeotic genes is important to determine segmental-specificity of NB6-4 daughter cells along the anterior-posterior (A/P) axis.